Nuttalliella namaqua (Ixodoidea: Nuttalliellidae): first description of the male, immature stages and re-description of the female. - Abdalla A Latif; John F Putterill; Daniel G de Klerk; Ronel Pienaar; Ben J Mans (PLoS ONE, 2012)
Nuttalliella namaqua is the only species of the enigmatic third tick family. Females possess features of hard and soft ticks and have been designated as the "missing link" between the main tick families. Its position at the base of the tick tree suggests that some of the features unique to hard and soft ticks were present in the ancestral tick lineage. Larvae, nymphae and males have not been described to date and questions regarding their biological affinities to the main tick families remain unclear. The current study addressed these questions via the description of larvae, nymphae and males and resolved issues pertaining to female morphology. Field collected as well as laboratory-engorged females laid eggs and viable larvae subsequently hatched. The larvae possess morphological structures not present in subsequent stages: namely, a sclerotized scutum, pores on the dorsal surface of legs and a dentate anal plate. The last two characters are not present in ixodids and argasids. N. namaqua larvae and nymphae show a similar morphology to females: a unique hypostomal structure i.e., bluntly rounded apically in nymphae and females and ball-like in the larvae. A re-description of some structures in female N. namaqua has resolved differences in the original descriptions, namely that N. namaqua have 4 palpal segments as found in ixodids and argasids and posthypostomal setae. The male was discovered for the first time and described. Characteristic male features include: a pseudoscutum over most of the dorsum, an outgrowth on the chelicerae forming a unique rod-like structure similar to a spematodactyl in mites and medial extension of palpal segment 2 forming a large ventral crib for segment 4. All life stages possess some features found in hard and soft ticks and its status as the "missing link" between the tick families remains.